Time-resolving the UV-initiated photodissociation dynamics of OCS. (11th February 2021) - Karamatskos, Evangelos T.; Yarlagadda, Suresh; Patchkovskii, Serguei; Vrakking, Marc J. J.; Welsch, Ralph; Küpper, Jochen; Rouzée, Arnaud
Abstract : We time-resolved the UV-induced photodissociation of OCS at λ = 237 nm through pump-probe ion imaging. Abstract : We present a time-resolved study of the photodissociation dynamics of OCS after UV-photoexcitation at λ = 237 nm. OCS molecules ( X 1 Σ + ) were primarily excited to the 1 1 A ′′ and the 2 1 A ′ Renner–Teller components of the 1 Σ − and 1 Δ states. Dissociation into CO and S fragments was observed through time-delayed strong-field ionisation and imaging of the kinetic energy of the resulting CO + and S + fragments by intense 790 nm laser pulses. Surprisingly, fast oscillations with a period of ∼100 fs were observed in the S + channel of the UV dissociation. Based on wavepacket-dynamics simulations coupled with a simple electrostatic-interaction model, these oscillations do not correspond to the known highly-excited rotational motion of the leaving CO( X 1 Σ +, J ≫ 0) fragments, which has a timescale of ∼140 fs. Instead, we suggest to assign the observed oscillations to the excitation of vibrational wavepackets in the 2 3 A ′′ or 2 1 A ′′ states of the molecule that predissociate to form S( 3 P J ) photoproducts.